Factor substitution and development path of the new energy market in the BRICS countries under carbon neutrality: Inspirations from developed European countries. (1st February 2023) - Pan, Yuling; Dong, Feng
Highlights: BRICS countries exhibit expansionary strategies in solar and wind power. DE countries exhibit conservative strategies in solar and wind power. The solar and wind power markets in BRICS countries are capital-oriented. BRICS countries should prevent the new energy technology dilemma. Abstract: Carbon neutrality is proposed by many countries for responding to climate change and energy transformation. Developing new energy is crucial to achieving carbon neutrality goals. In the context of carbon neutrality, this paper analyzes the factor structure and market orientation of the new energy market in BRICS countries (including the Federative Republic of Brazil, Russian Federation, the Republic of India, People's Republic of China, and the Republic of South Africa) and developed European (DE) countries in recent years. The primary conclusions are as follows: (1) In wind and solar energy markets, the BRICS countries exhibit an elastic substitution effect in production, indicating they have chosen the expansionary strategy with unbalanced factors. Through the contribution analysis, we find the development of wind and solar energy in BRICS countries is capital-oriented. However, the DE countries have opted for a conservative strategy with balanced factors, in which the wind and solar energy markets need promotional measures for capital investment and technological progress. (2) In the biomass energy market, both the BRICS countries and DE countries adopt the expansionary strategy. Besides, the development of the biomass energy market is technology-oriented except for India. (3) For the nuclear energy market, the BRICS countries and DE countries choose the conservative strategy and expansionary strategy, respectively. However, due to safety concerns, the expansion of nuclear energy in all countries has slowed. (4) Although a capital-oriented strategy can quickly promote the development of the new energy market, this practice compromises the local welfare and the benefits of the new energy technology progress to varying extents. The core insight of this paper is that BRICS countries should avoid the new energy capital trap and prevent the new energy technology dilemma. For the BRICS countries, policymakers should further evaluate the balance between capital-oriented interest and technology-oriented development. Also, achieving carbon neutrality is more difficult for the BRICS countries than DE countries. Hence, the BRICS countries should further refine their energy strategies for the long term.